Virtual Tour Panorama 360° Sebagai Media Infomasi Kampus Universitas Nusa Putra - Azia Nurfikri; Alun Sujjada; Simatupang, Dwi Sartika (Computer Science and Information Technology, 2023)
Nusa Putra University is one of the universities in Sukabumi that is experiencing a significant increase in the admission of new students from different regions every year. With the increase in the number of students, it is important to have adequate information facilities. Virtual tour is one of the current technological innovations. This technology allows users to view and explore the environment online. It provides an immersive experience for users. This thesis aims to create a website that provides a 360-degree panoramic virtual tour of Nusa Putra University's campus area. The application development process uses the Multimedia Development Life Cycle (MDLC), which consists of six phases: concept, design, material collecting, assembly, testing, and distribution. The development of a virtual tour will display campus environment information that can be accessed through the website, which can guide users to find information in every corner of the campus area with 360-degree panoramic image media. The results of this study indicate that users respond positively to this virtual tour applications, based on the results of functionality testing using the black box method, which obtained a percentage of feasibility of 99,47%, and the results of usability testing using the System Usability Scale (SUS) method, which obtained a percentage of feasibility of 94,08%, which means that the system is very feasible to use and works well and can be easily used by users